The vaults of Arronches Nossa Senhora da Assunção and Misericórdia churches. Geometric and constructive comparison with the nave and refectory vaults of Jerónimos Monastery - Genin, Soraya M. (Thinking, Drawing, Modelling, 2020)
The comparison between the vaults of the Arronches Nossa Senhora da Assunção church and the Jerónimos monastery church was first performed by Mário Tavares Chicó [1]. He noticed how the naves and side aisles were covered by a single curved shape, unique in Europe. Mendes Atanázio attributed both authorships to one architect: João de Castilho (c.1470–1552). The architectural analysis of both vaults concluded that there were several geometrical similarities, particularly in relation to their elevation and their gothic proportions. Arronches Misericórdia church was built in the same period as the Assunção church. It is covered by a liernes vault, similar to the refectory vault of the Jerónimosmonastery. The geometric analysis of both vaults shows a similar design, in plan and in elevation. The geometric analysis of the vaults was obtained from architectural surveys. Design and construction hypothesis presented were developed using the methods of Hernán Ruiz (1500–1569) and Rodrigo Gil de Hontañón (1500–1577). They were both Spanish architects, contemporaries of João de Castilho.